Confessions of the dead [large type] - Patterson, James, 1947-; Barker, J. D. (Jonathan Dylan), 1971- (Grand Central Publishing, 2024)
Hollows Bend, New Hampshire, is a picture-perfect New England town where weekend tourists flock to see fall leaves and eat breakfast at the Stairway Diner. The crime rate--zero--is a point of pride for Sheriff Ellie Pritchett. The day the stranger shows up is when the trouble starts. The sheriff and her deputy investigate the mysterious teenage girl. None of the locals can place her. She can't--or won't-answer any questions. She won't even tell them her name. While the girl is in protective custody, the officers are called to multiple crime scenes leading them closer and closer to a lake outside of town that doesn't appear on any map.